Nanostructure lipid carriers: A modish contrivance to overcome the ultraviolet effects - Priyanka Jain; Prerna Rahi; Vikas Pandey; Saket Asati; Vandana Soni (2017)
Protection of the skin from the ultraviolet radiation is the prime concern of society. An increase in the adverse effects by ultraviolet (UV) radiation on the skin promoted cosmetic formulators to work in the area of UV blockers and their effective means of delivery. Nanostructured lipid carriers (NLCs) is a modern and successful lipid carrier system in the cosmetic world associated with various advantages i.e., stability, effective drug loading capacity etc. NLCs also permits to load 70% of UV blockers which are sufficient to obtain recommended Sun Protection Factor (SPF) which makes them suitable delivery systems for topical application of the UV blockers.